Comparison of clinical efficacy and safety between salbutamol-ipratropium bromide nebulization and salbutamol alone in children with asthmatic attack - Lusiana Kartininingsih; Landia Setiawati; Makmuri M S (Paediatrica Indonesiana, 2006)
Background Indonesian guidelines for childhood asthma recom-mend giving ipratropium bromide when there are no improvementafter 2 times salbutamol nebulization. The efficacy and safety ofearly nebulization of ipratropium bromide combined with salbutamolas first line in moderate asthma exacerbation in children are stillunknown.Objective To compare efficacy and safety between nebulizedsalbutamol-ipratropium bromide and salbutamol alone in childrenwith moderate asthma exacerbation.Methods Fifty-two children (2-6 years) with acute asthma (clinicalscore 5-10) were enrolled into a randomized single blind controlledtrial comparing 2 groups of 2.5 mg nebulized salbutamol (group 1)and 2.5 mg salbutamol combined with 0.5 mg ipratropium bromide(group 2). Nebulization was given until clinical score decreased<5, maximum of 3 doses during 2 hours. Clinical measurementsincluded clinical score, oxygen saturation and side effects whichwere assessed every 20 minutes up to 120 minutes. Statisticaltest for homogeneity and comparison of clinical outcomes and sideeffects used independent t-test, Fisher’s exact test, and Mann-Whitney U test (P<0.05).Results The groups were similar in all baseline measures. Therewere significantly decreasing clinical score in groups 2 at 20, 40,60, 80, 100, and 120 minutes (P<0.05), and the means of oxygensaturation were significantly higher in group 2 at 20, 40, 60, 80,100, and 120 minutes (P<0.05). In group 1, 11.5% of patients werehospitalized after the study and none in groups 2 (P> 0.05). Therewere no toxic effects attributable to ipratropium bromide, and theside effects were not different between these two groups.Conclusion The combination of nebulized ipratropium bromideand salbutamol in a child with acute moderate asthma exacerba-tion was associated with higher reduction of clinical score and higheroxygen saturation, and may reduce hospitalization